KEPENTINGAN POLITIK PEMERINTAH PUSAT DAN PROVINSI DKI JAKARTA DALAM PENANGANAN PENURUNAN TANAH JAKARTA: STUDI KASUS KEBIJAKAN TANGGUL RAKSASA DI JAKARTA UTARA - Muhamad Fatih Praga Ilhaq; Daud Yunus S; Atiqah Shabrina; Achmad Fernanda (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2021)
Implementing a giant sea wall in North Jakarta is one of the solutions to reduce land subsidence in Jakarta, according to geodesy’s research from ITB and UNDIP 95% that area of North Jakarta will sink by 2050. This research used elite theory and case study of qualitative methods, the authors used the Central Government and the Government of DKI Jakarta as research samples and saw how their interests are in implementation of the giant sea wall in North Jakarta. Since the beginning of implementation in 2015, it has faced political obstacles. The political obstacles are, none of definite regulation from Jakarta’s Government, discrepancy interests between Central Government and Provincial Government, and power struggle in Jakarta.